Violencia de género en estudiantes del Área de la Salud Humana de la Universidad Nacional de Loja, en el periodo académico marzo-julio de 2016. - Torres Jaramillo, Cyndi Maribell (2017)
Gender violence is a social problem that deeply affects the life project of many people, particularly women and girls, impacting the development of communities and society. The objectives of this investigation were directed to Establish the percentage and gender of students violated in the Human Health Area of the National University of Loja; To determine the methods of access and attention to the health services to the student or the violated student, To establish the level of knowledge that the students present about gender violence and its consequences and the Dissemination of the results obtained to the university authorities and students. This descriptive, qualitative quantitative study was carried out with the application of the Gender Violence Questionnaire to 299 students. The results obtained showed that 36.1% were women raped, it is evident that violent episodes perceived by college students were by the previous brides, representing 25% (n = 22). In university students, most of the violence received was by the previous boyfriends by 16% (n = 34). It was investigated on the actions that would take the student, against the violence of gender, the 46.8% would break the relation. The majority of knowledge about the issue of gender violence, university students have acquired 24.08% of the Internet (n = 72). Gender-based violence can affect both men and women, with women being the most affected, knowledge about gender-based violence is very limited at the university level, so its importance is underestimated, and the impact is not only on a personal level , but in the health system and in society. Keywords: violence, gender, sexism, woman, man.